Millennium : The Complete First Season Disc 1 - Carter, Chris; Tiplady, Brittany, 1991-; Klea Scott; Megan Gallagher; Terry O'Quinn; Lance Henriksen (USA 20th Century Fox, 1996)
A former FBI profiler moves his family from Washington DC to Seattle, where he joins the Millenium Group, a mysterious organization of former law enforcement officers, committed to battling a crime wave which grows as the turn of the millenium approaches.
A former FBI profiler with the ability to look inside the mind of a killer begins working for the mysterious Millennium Group.
Language : English Subtitles : English
Keywords: Drama; Horror; Mystery; Thriller -- Tv Series; Crime